2014
DOI: 10.21608/ejabf.2014.2199
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Biology of little tunny, Euthynnus alletteratus (Rafinesque 1810) in the Eastern Coast of Alexandria, Egypt

Abstract: Reproductive biology of Euthynnus alletteratus was described based on 628 fishes that were collected from Abu Qir landing site between October 2006 and September 2007. Only 146 specimens were sexually distinguished (102 females, 44 males) and the others were immature. The sex ratio was estimated as M: F 1:2.3. Size at first sexual maturity was estimated as 42cm. Spawning season was investigated based on monthly observation of gonadal maturity stages and gonad-somatic index (GSI). The spawning season extends fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…If the existing information between ETA and NETAM areas is compared, in a study carried out in the ETA area, a very extensive spawning period is observed, which occupies practically the whole year [47]. However, in the Mediterranean Sea, the period is quite seasonal and limited, coinciding with the warmer period, between the months of June and August [49][50][51]69]. However, both biological aspects must be studied in depth in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the existing information between ETA and NETAM areas is compared, in a study carried out in the ETA area, a very extensive spawning period is observed, which occupies practically the whole year [47]. However, in the Mediterranean Sea, the period is quite seasonal and limited, coinciding with the warmer period, between the months of June and August [49][50][51]69]. However, both biological aspects must be studied in depth in the future.…”
Section: Discussionmentioning
confidence: 99%
“…According to the ICCAT official catch statistics, this species account for a significant proportion of the total small tuna species production, representing in the last years around 15% of the total catch [37]. Diverse biological information on this species is available focusing on age and growth [38][39][40][41][42][43][44], reproduction [45][46][47][48][49][50][51], and stock assessment [32,35]. However, concerning stock structure, there are some knowledge gaps with a lack of concise information on this species [43,44].…”
Section: Introductionmentioning
confidence: 99%